Impact of land administration on private housing delivery in Lagos, Nigeria / Joseph Oyewale Oyedeji - Oyedeji, Joseph Oyewale (UiTM Press, 2021)
Previous studies on impact of land administration on housing delivery had only examined impact of some of the functions of land administration on housing delivery and not impact of the four functions of land administration on housing delivery. This study filed this gap by examining the impact of the four functions of land administration on private housing delivery in Lagos, Nigeria. The study population is members of Real Estate Developers Association of Nigeria (REDAN). The population size is 1400 and systematic random sampling technique was employed to have a sample size of 140. 120 questionnaires were retrieved and reliable for analysis. Data gathered were analyzed through descriptive statistics, tables, mean and multiple regressions. Findings from the study revealed that reduction in quantity produced is the most prominent impact of land tenure, delay in time of housing delivery is the impact of land use and land development and change in location of property is the most prominent impact of land taxation. Also, the most prominent problem of land administration is lack of computerized land administration system. The study established that land administration has significant impact on private housing delivery. It was recommended that bureaucracy that surrounds land administration should be reduced in order to reduce associated time and cost. Also, the land administration system should be computerized for easy land administration services. Keywords: Land, Land administration, Housing, Housing Delivery, Lagos